KELELAHAN KERJA SEBAGAI MEDIATOR ANTARA BEBAN KERJA DAN MOTIVASI KERJA - Mardiyanto Mardiyanto; Siska Adinda Prabowo Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2024)
This study aims to determine and analyze the relationship between workload and work motivation mediated by work fatigue. The population in this study were members of Samapta and members of Lantas Polres Pekalongan City totaling 120 people. The number of samples used was the same as the population. The sampling technique used was saturated sampling. The analysis used was multivariate regression analysis. Work motivation in this study was measured using a Likert scale based on aspects of work motivation from Herzberg. The workload variable was measured using a Likert scale based on the workload dimension theory from Hart & Staveland. Fatigue was measured using the Subjective Self Rating Test questionnaire. The results of this study indicate that workload has a positive and very significant effect on work fatigue, work fatigue has a negative and very significant effect on work motivation, workload has no direct effect on work motivation and workload has a very significant effect on work motivation mediated by work fatigue. The coefficient of determination in this study is indicated by the value of R2 = 0.172 or 17.2%, which means that workload and work fatigue affect work motivation by 17.2% and the remaining 82.8% is influenced by other factors. Keywords: Work motivation, Work fatigue, Workload